Apathy in late-life depression among Taiwanese patients - Lee, Shwu-Hua; Wen, Ming-Ching; Chao, Chia-Chen; Chen, Ying Jen; Yen, Cheng-Fang (International psychogeriatrics, 2008)
Background: Apathy is defined as lack of motivation and occurs in a variety of neuropsychological disorders. The Apathy Evaluation Scale (AES) has been shown to be valid and reliable for assessing apathy in depression but the validity and reliability of the Chinese version has never been examined. The aims of the study were to (1) evaluate the validity and reliability of the Chinese version of the AES in late-life depression and (2) evaluate the severity of apathy in late-life depression. Methods: We translated the AES into Chinese and used a cross-sectional design to evaluate apathy in elderly subjects. Diagnostic and Statistical Manual of Mental Disorders (DSM) -IV criteria and Hamilton Depression Rating Scale (HDRS) were applied for diagnosis and assessment. Three groups of subjects were recruited including one group (n = 31) of patients with major depressive disorder with current depression, the second group (n = 30) with major depressed disorder with remission, and the third group (n = 31) of healthy controls. Convergent validity was tested using four apathy-related items from the HDRS (loss of interest, psychomotor retardation, loss of energy, and loss of insight). Multiple forms of reliability (including internal consistency, test-retest, and interrater) and discriminant validity were examined. Results: We demonstrated that the internal consistency (coefficient α = 0.90) and test-retest reliability (p < 0.001) were satisfied. Discriminant validity of apathy severity among these three groups was significant. The convergent validity and correlation coefficients based on the four apathy-related items from the HDRS and AES were acceptable. Conclusion: Apathy is a distinct syndrome which may be treatable when depression is effective managed. Further application of the Chinese version of the AES to study the association of apathy with other neuropsychological symptoms is necessary.